2005
DOI: 10.1650/7858.1
|View full text |Cite
|
Sign up to set email alerts
|

Plumage Convergence in Picoides Woodpeckers Based on a Molecular Phylogeny, With Emphasis on Convergence in Downy and Hairy Woodpeckers

Abstract: Abstract. Adult and juvenile plumage characters were traced onto a well-resolved molecular based phylogeny for Picoides woodpeckers, and a simple phylogenetic test of homology, parallelism, and convergence of plumage characters was performed. Reconstruction of ancestral character states revealed multiple events of independent evolution of derived character states in most characters studied, and a concentrated changes test revealed that some plumage characters evolved in association with habitat type. For examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…He concluded that these plumage similarities were evidence of recent shared ancestry, in that ''the complexity of these color patterns precludes any reasonable possibility of their arising independently in three pairs of genera; no known selection forces could explain such a pattern of convergence.'' Over the past decade, molecular phylogenetic analyses have confirmed that the inverse is the case, documenting convergent evolution of phenotypic traits in 11 picid genera, and now our data provide yet another example in which plumage convergence in the Helmeted Woodpecker has confounded phylogenetic relationships in the Malarpicini (Webb and Moore 2005, Weibel and Moore 2005, Benz et al 2006, Moore et al 2006, Fuchs et al 2008. Although some uncertainty remains with respect to branching patterns among primary Celeus clades, our mitochondrial and nuclear data strongly support inclusion of D. galeatus within the genus (Figures 3 and 5).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…He concluded that these plumage similarities were evidence of recent shared ancestry, in that ''the complexity of these color patterns precludes any reasonable possibility of their arising independently in three pairs of genera; no known selection forces could explain such a pattern of convergence.'' Over the past decade, molecular phylogenetic analyses have confirmed that the inverse is the case, documenting convergent evolution of phenotypic traits in 11 picid genera, and now our data provide yet another example in which plumage convergence in the Helmeted Woodpecker has confounded phylogenetic relationships in the Malarpicini (Webb and Moore 2005, Weibel and Moore 2005, Benz et al 2006, Moore et al 2006, Fuchs et al 2008. Although some uncertainty remains with respect to branching patterns among primary Celeus clades, our mitochondrial and nuclear data strongly support inclusion of D. galeatus within the genus (Figures 3 and 5).…”
Section: Discussionsupporting
confidence: 68%
“…Recent progress in assembling the avian tree of life has shed light on numerous instances of nonaposematic plumage convergence in disparate taxonomic groups (Weckstein 2005, Weibel and Moore 2005, Tello et al 2009, Jønsson et al 2010. The highest incidence, and perhaps the most comprehensive examples, of this phenomenon occur within the woodpeckers (Picidae), which exhibit convergent evolution of elaborate plumage patterns in !11 genera (Webb and Moore 2005, Weibel and Moore 2005, Benz et al 2006, Moore et al 2006, Fuchs et al 2008.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…51 Woodpeckers are well known as ecosystem engineers, excavating 52 tree cavities that are subsequently used by numerous other species 53 of animals (Aitken and Martin, 2007;Cockle et al, 2011;Martin 54 and Eadie, 1999). The group also includes striking examples of 55 visual mimicry and convergent evolution (Benz et al,in press;56 Cody, 1969;Lammertink et al, 2015;Moore et al, 2006;Prum, 57 2014; Prum and Samuelson, 2012;Weibel and Moore, 2005;58 Winkler et al, 2014). A comprehensive species-level phylogeny 59 of the family is needed in order to more fully understand their bio-60 geography, convergence, morphological evolution and the evolu-61 tion of foraging modes and cavity-excavating behavior.…”
mentioning
confidence: 99%